Agrarian change and well-being status of Mara tribe in Mizoram - PANDEY, D K; DE, H K; KUMAR, PRABHAT; DUBEY, S K (The Indian Journal of Agricultural Sciences, 2019)
This study is focused on the agrarian change and well-being status among Mara hill tribe practicing Shifting Cultivation (SC) in Saiha, a remote Hill district in North Eastern Region of India. Using a mixed methods research design, 50 tribal households were interviewed with the help of structured interview schedule. The findings reveal transition in terms of aversion of the tribal youths from SC, declining dependency of the community on SC and fare share (37.16%) of total expenditure on children’s education. Further, increased access to information gadgets like mobile phone, TV and radio are triggering material aspirations among the tribal community. The average monthly income of respondent households was about ` 10766 and 77.56% of the total income is contributed by agriculture and allied activities. Higher inclination was observed towards settled cultivation with high value horticultural crops, however, community ownership of land, lack of market access and higher technological gap in agriculture were impeding entrepreneurship. The study reveals that well-being of 93% tribal households were moderate or inconsistent. They are experiencing difficulties as on date and are also expected to continue with it in the near future. Hence, planning and implementation of development schemes focused on welfare and livelihood diversification need to be revisited to enhance overall well-being of the hill tribe who rely on SC for their livelihood.